Telegram from J. Widdicombe [Willicombe] to Julia Morgan, May 20, 1920 - Joseph Willicombe::::::author::: (1920)
Telegram from William Randolph Hearst's secretary, J. Willicombe (misspelled as Widdicombe by the telegram operator), to Julia Morgan